COVID-19, Authoritarian Neoliberalism, and Precarious Migrant Work in Singapore: Structural Violence and Communicative Inequality - Dutta, Mohan Jyoti (Frontiers in Communication, 2020)
Drawing upon an ongoing ethnography with low-wage migrant workers in Singapore, this article builds on the theoretical framework of the culture-centered approach (CCA) to explore the experiences of the workers amid COVID19 outbreaks in dormitories housing them. The CCA foregrounds the interplays of communicative and material inequalities, suggesting that the erasure of infrastructures of voices among the margins reproduces and circulates unhealthy structures that threaten health and wellbeing. The voices of the low-wage migrant workers who participated in this study document the challenges with poor housing, poor sanitation, andfood insecurity, that are compounded with the absence of information and voice infrastructures. Amid the everyday precarities that are generated by neoliberal reforms across the globe, the hyper-precarious conditions of migrant work rendered visible by the trajectories of COVID19 call for structurally transformative futures that are anchored in the voices of workers at the margins of neoliberal economies.